Molecular characterisation of the rotavirus strains prevalent in Maua, Meru North, Kenya - Kiulia, NM; Peenze, I; Dewar, J; Nyachieo, A; Omolo, E; Steele, AD; Mwenda, JM (East African medical journal, 2006)
Rotavirus is the most common cause of severe infantile diarrhoea disease in infants and young children below five years worldwide. Rotavirus is associated with high cases of morbidity and mortality and it is estimated that up to 650,000 deaths in young children occur annually in the less developed countries and approximately 150,000-200,000 deaths occur in Africa alone. To characterise the circulating rotavirus strains in Maua, Meru North district, Kenya. A prospective study to investigate and characterise rotavirus serotypes/genotypes and electropherotypes in infants and children with severe diarrhoea hospitalised and/or attending the outpatient department of Maua Methodist Hospital during the period April 2004 to September 2005. Maua Methodist Hospital, Meru North, Kenya. Faecal samples were collected from 135 infants and children with acute diarrhoea and were screened first for the presence of human Group A rotavirus antigen using commercially available enzyme linked immunosorbent assay kit (ELISA). The positive samples were evaluated by sodium dodecyl polycrylamide gel electrophoresis (SDS-PAGE) to determine the viral RNA electropherotype profile. Rotavirus strains were also genotyped using reverse transcriptase polymerase chain reaction (RT-PCR) of the VP7 gene. Assay of these samples with commercial ELISA showed that 17.8% (24/135) were positive for group A rotavirus antigen. Twenty of these ELISA positive samples were also analysed by SDS-PAGE of which 75% (15/20) gave detectable electropherotype pattern with the long electropherotype being predominant 80.0% (12/15) followed by the short RNA profile 20.0% (2/ 15). Seventeen of the ELISA positive samples were genotyped for VP7 and the results showed that G9 was the most predominant genotype comprising 47.1% (8/17) followed by G8 29.4% (5/17), GI 17.4% (3/17) and the mixed genotype was G8/G9 5.9% (1/17). Most patients with rotavirus infection were of the age of 3 - 60 months, with 79% being less than 18 months old. The overall prevalence of rotavirus infection in young children with diarrhoea hospitalised and/or attending the out-patient department of Maua Methodist Hospital was 17.8% with the predominant serotype being G9. These results show that rotavirus plays an important role in severe viral diarrhoea in young children in Maua Meru North district, Kenya. Furthermore, this high G9 rotavirus prevalence in Kenya may require vaccine trials to be held in Kenya so as to determine the efficacy of new rotavirus vaccine candidates that do not include the G9 serotype.